A Prospective International Study on Adherence to Treatment in 305 Patients With Flaring SLE: Assessment by Drug Levels and Self‐Administered Questionnaires. Issue 6 (9th November 2017) - Costedoat‐Chalumeau, Nathalie; Houssiau, Frédéric; Izmirly, Peter; Le Guern, Véronique; Navarra, Sandra; Jolly, Meenakshi; Ruiz‐Irastorza, Guillermo; Baron, Gabriel; Hachulla, Eric; Agmon‐Levin, Nancy; Shoenfeld, Yehuda; Dall'Ara, Francesca; et al.
Abstract : Nonadherence to treatment is a major cause of lupus flares. Hydroxychloroquine (HCQ), a major medication in systemic lupus erythematosus, has a long half‐life and can be quantified by high‐performance liquid chromatography. This international study evaluated nonadherence in 305 lupus patients with flares using drug levels (HCQ <200 ng/ml or undetectable desethylchloroquine), and self‐administered questionnaires (MASRI <80% or MMAS‐8 <6). Drug levels defined 18.4% of the patients as severely nonadherent. In multivariate analyses, younger age, nonuse of steroids, higher body mass index, and unemployment were associated with nonadherence by drug level. Questionnaires classified 39.9% of patients as nonadherent. Correlations between adherence measured by questionnaires, drug level, and physician assessment were moderate. Both methods probably measured two different patterns of nonadherence: self‐administered questionnaires mostly captured relatively infrequently missed tablets, while drug levels identified severe nonadherence (i.e., interruption or erratic tablet intake). The frequency with which physicians miss nonadherence, together with underreporting by patients, suggests that therapeutic drug monitoring is useful in this setting. (Trial registration:ClinicalTrials.gov : NCT01509989.)